Proton exchange membranes prepared by simultaneous radiation grafting of styrene onto poly(tetrafluoroethylene-co-hexafluoropropylene) films. II. Properties of sulfonated membranes - Nasef, Mohamed Mahmoud; Saidi, Hamdani; Mohd Nor, Hussin; Ooi, Mun Foo (John Wiley & Sons, Inc., 2000)
Proton exchange membranes were prepared by radiation-induced grafting of styrene onto commercial poly(tetrafluoroethylene-co-hexafluoropropylene) films using a simultaneous irradiation technique followed by a sulfonation reaction. The resulting membranes were characterized by measuring their physicochemical properties such as water uptake, ion exchange capacity, hydration number, and proton conductivity as a function of the degree of grafting. The thermal properties (melting and glass transition temperatures) and thermal stability of the membrane were also investigated using differential scanning calorimetry and thermal gravimetric analysis, respectively. Membranes having degrees of grafting of 16%and above showed proton conductivity of the magnitude of 1022 V21 cm21 at room temperature, as well as thermal stability at up to 290Â°C under an oxygen atmosphere.